Pretty modern : beauty, sex, and plastic surgery in Brazil - Edmonds, Alexander, 1970- (e-Duke books scholarly collection., 2010)
Pretty Modern is a riveting account of Brazil's emergence as a global leader in plastic surgery. Intrigued by a Carnaval parade that mysteriously paid homage to a Rio de Janeiro plastic surgeon, anthropologist Alexander Edmonds conducted research that took him from Ipanema socialite circles to glitzy telenovela studios to the packed waiting rooms of public hospitals offering free cosmetic surgery. The result is provocative exploration of the erotic, commercial, and intimate aspects of beauty in a nation with extremes of wealth and poverty and a reputation for natural sensuality. Drawing on conversations with maids and their elite mistresses, divorced housewives, black celebrities, and favela residents aspiring to be fashion models, Edmonds analyzes what sexual desirability means and does for women in different social positions. He argues that beauty is a distinct realm of modern experience that does not simply reflect other inequalities. It mimics the ambiguous emancipatory potential of capital, challenging traditional hierarchies while luring consumers into a sexual culture that reduces the body to the brute biological criteria of attractiveness. Illustrated with color photographs, Pretty Modern offers a fresh theoretical perspective on the significance of female beauty in consumer capitalism.